Image reconstruction of metal pipe in electrical resistance tomography - Ridzuan Aw, Suzanna; Abdul Rahim, Ruzairi; Mohd Yunus, Yusri; Rahiman, Mohd Hafiz Fazalul; Wahab, Yasmin; Mohd Yunus, Fazlul Rahman; Mohamed, Elmy Johana; Abdul Aziz, Azian; Chiew, Loon Goh; Pusppanathan, Jayasuman; Green, R. G.; Zhen, Cong Tee (International Frequency Sensor Association (IFSA) Publishing, 2017)
This paper demonstrates a Linear Back Projection (LBP) algorithm based on the reconstruction of conductivity distributions to identify different sizes and locations of bubble phantoms in a metal pipe. Both forward and inverse problems are discussed. Reconstructed images of the phantoms under test conditions are presented. From the results, it was justified that the sensitivity maps of the conducting boundary strategy can be applied successfully in identifying the location for the phantom of interest using LBP algorithm. Additionally, the number and spatial distribution of the bubble phantoms can be clearly distinguished at any location in the pipeline. It was also shown that the reconstructed images agree well with the bubble phantoms.